Catalogação e descrição de documentos fotográficos em bibliotecas e arquivos: uma aproximação comparativa dos códigos AACR2 e ISAD (G) - Albuquerque, Ana Cristina de [UNESP] (2006)
This work boards the photographic document in the scope of its description in archives and libraries. The objective is to make possible the comparison between the AACR2 rules, utilized for bibliographic description in libraries and the ISAD (G) norm, which are the rules to obtain an archivist description. Departing from document concept, passing by his function in archives and libraries and passing by photography history. This is the object context in a first moment, leading to the presentation of AACR2 rules and ISAD (G), until the electronic cataloguing which is possible by the use of MARC 21 format. This way, some elements of photographic document bring in its composition and support is described, because through his various physical characteristics we found part of the particularities that instigate countless discussions about it. In front of the referred theoric basis, a panoramic analysis of the present rules is made following the representation ways for each one: for the librarianship, its cards materialize the description act and make available the item in the collection and, to archival science, its tools of research which, in the same way, offer to the users a view not only of the material but his context in the collection. At last, is reached an approach of points in the two norms worthily attention and a profound study by researchers and professionals working the photographic document. Under archivist's principles and librarian treatment theory, there is a consideration about description in general form and its application in a document with peculiarities and when the document is target of discussions that reflect in availability to the users an its studies generally.